Comparative Estimation of Some Contaminates in Products of Drinking Water Companies and Government Stations in the City of Mosul - Maseer Nejres, Aws (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2025)
Recently, the concentrations of heavy metals have increased in water sources, soil and air, and their symptoms have clearly appeared on living organisms and the serious effects they leave on humans, animals and even plants. has become necessary to periodically monitor these metals, including nickel (Ni), cadmium (Cd), lead (Pb)and cobalt (Co). However, the problem does not stop with heavy metals, as there are other parameters that are closely related in one way or another, such as hardness, pH, Total dissolved solids (TDS) and even conductivity (EC), All of these are present in the water under study, in addition to the Microbiological Assessment test to search for pathogens. The environment of Mosul city was chosen as a source for collecting samples from three categories: local water projects, reverse osmosis water sales systems, in addition to companies accredited for sterilizing, bottling and marketing water. These Metals and parameters were studied using an atomic absorption device, and the results were within the limits established in the regulations of international organizations and bodies.